Eksekutif wanita, struktur kepemilikan, dan manajemen laba - Raharjo, Kharis (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of female CEOs, female CFOs, blockholder ownership, management ownership and institutional ownership on earnings management. A sample of 892 pooled data from manufacturing companies listed on the Indonesia Stock Exchange 2015-2020 obtained by purposive sampling. Research data in the form of documentation of financial statements and annual reports obtained at www.idx.co.id or the website of the company concerned. The data were then analyzed using multiple linear regression analysis. The results of the study are female CEOs, blockholder ownership and institutional ownership have a negative effect on earnings management, while female CFOs and management ownership have no effect on earnings management. The research implication is the need to consider gender diversity in executive positions to reduce earnings management, as well as the supervisory role of blockholder and institutional stockholders to reduce earnings management.